Hubungan Sosiodemografi dan Gaya Hidup Masyarakat Usia 30-65 Tahun dengan Kejadian Hipertensi di UPT. Puskesmas Securai Kabupaten Langkat Tahun 2025 - Rosadi, Tasya; Hiswani, Hiswani (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to examine the relationship between sociodemographic factors and lifestyle with the incidence of hypertension among individuals aged 30–65 years at UPT. Puskesmas Securai Langkat Regency in 2025. The study used a cross-sectional design with a total of 135 respondents selected through purposive sampling. Data were collected through interviews using structured questionnaires. Bivariate analysis using the chi-square test showed significant associations between hypertension and family history (p = 0,026), age (p = 0,006), sex (p = 0,053), ethnicity (p = 0,030), education level (p = 0,015), employment status (p < 0,001), income (p = 0,015), marital status (p = 0,003), body mass index (BMI) (p = 0,002), smoking habits (p = 0,031), and physical activity (p = 0,031). In contrast, alcohol consumption (p = 0,280) showed no significant relationship with hypertension. These findings suggest that most sociodemographic and lifestyle factors are associated with the incidence of hypertension. Therefore, targeted health promotion and preventive efforts should focus on individuals at higher risk through proper education and community-based interventions.